NOTARY’S RESPONSIBILITY TO THE TRUTH OF DATA IN THE MAKING OF ISLAMIC BANKING CONTRACT IN INDONESIA - Abdul Muin (UNISSULA, 2018)
Notary is a public official appointed by the government authorized to make an authentic deed as stipulated in UUJN. Authority as mentioned above includes in the making of deed or contract on Islamic Banking. A contract according to language is binding, connecting, as for the meaning of the contract by term is an association or meeting between ijab and qabul that result in law. While the definition of Islamic Banking is a bank that runs its operations based on the principles of sharia. Notary Authority as regulated in Law Number 30 Of 2004 junto Law Number 2 Of 2014 concerning Notary Position shall be based on the honesty of Notary in executing its duties and authority including within the truth of the data in the process of making the contract. If the contract or deed made by the Notary in the future found the supporting data proved counterfeit and Notary participate in the practice of data forgery then the Notary is the person involved in making the contract with false data. However, if the data on which the notarial deed is made is not involved in the falsification, then the Notary does not take responsibility in the criminal act of falsifying the data. And the notary may exercise its right of interest. The legal basis of this journal is the Qoran and Hadits, Law No. 30 of 2004, Law No. 2 of 2014 on the position of Notary, Law Number 31 Of 2008 concerning Islamic Banking and the Civil Code.